INTEGRASI ILMU PENDIDIKAN DAN PKN DALAM PENGUATAN KOMPETENSI SOSIAL MAHASISWA PGMI - Anggriyani, Farida Catur Wahyu (STAI Sangatta Kutai Timur, 2025)
This study aims to analyze the integration of educational science and Civics (PKn) in the learning process of students of the Elementary Madrasah Teacher Education Study Program (PGMI) at STAI Sangatta, and to examine the implementation of this integration in strengthening students' social competence. This study uses a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation of lecturers and PGMI students involved in integrative learning activities. The results show that the integration of educational science and Civics is carried out through the development of a thematic curriculum, the implementation of learning based on national and Islamic values, and collaborative activities that foster positive social attitudes in students. This integration contributes to strengthening students' social competence, which is reflected in increased cooperation, tolerance, communication, and social awareness. Supporting factors include lecturer commitment, institutional support, and synergy between courses; while inhibiting factors include limited lecture time and a lack of contextual learning media. This study emphasizes the importance of an integrative, cross-disciplinary approach in developing the social competence of prospective madrasah teachers